The uses of enchantment the meaning and importance of fairy tales - Bettelheim, Bruno (Vintage Books, 1977)
The great child psychologist gives us a brilliant and moving revelation of the enormous and irreplaceable value of fairy tales -- how they educate, support, and liberate the emotions of children.